Can Regenerative Agriculture increase national soil carbon stocks? simulated country-scale adoption of reduced tillage, cover cropping, and ley-arable integration using RothC - Jordon, MW; Smith, P; Long, PR; Bürkner, P-C; Petrokofsky, G; Willis, KJ (Elsevier, 2022)
Adopting Regenerative Agriculture (RA) practices on temperate arable land can increase soil organic carbon (SOC) concentration without reducing crop yields. RA is therefore receiving much attention as a climate change mitigation strategy. However, estimating the potential change in national soil carbon stocks following adoption of RA practices is required to determine its suitability for this. Here, we use a well-validated model of soil carbon turnover (RothC) to simulate adoption of three regenerative practices (cover cropping, reduced tillage intensity and incorporation of a grass-based ley phase into arable rotations) across arable land in Great Britain (GB). We develop a modelling framework which calibrates RothC using studies of these measures from a recent systematic review, estimating the proportional increase in carbon inputs to the soil compared to conventional practice, before simulating adoption across GB. We find that cover cropping would on average increase SOC stocks by 10 t·ha−1 within 30 years of adoption across GB, potentially sequestering 6.5 megatonnes of carbon dioxide per year (MtCO2·y−1). Ley-arable systems could increase SOC stocks by 3 or 16 t·ha−1, potentially providing 2.2 or 10.6 MtCO2·y−1 of sequestration over 30 years, depending on the length of the ley-phase (one and four years, respectively, in these scenarios). In contrast, our modelling approach finds little change in soil carbon stocks when practising reduced tillage intensity. Our results indicate that adopting RA practices could make a meaningful contribution to GB agriculture reaching net zero greenhouse gas emissions despite practical constraints to their uptake.